2019
DOI: 10.1080/15213269.2019.1598435
|View full text |Cite
|
Sign up to set email alerts
|

Acting your avatar’s age: effects of virtual reality avatar embodiment on real life walking speed

Abstract: When immersive virtual reality users employ digital selfrepresentations, i.e., avatars, they may be subject to the Proteus effect. This effect describes changes in attitudes and behaviors in accordance with identity cues derived from the employed avatar's appearance, which can persist after leaving virtual reality. Individual reactions to the experience can affect the strength of observed Proteus effects. Especially the experienced illusions of body ownership of avatars and of being in the virtual environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 44 publications
3
43
2
Order By: Relevance
“…Virtual reality offers the unique possibility to temporarily substitute participants' physical body with a virtual body (30), which can have very different characteristics than their own, such as a different age. Previous research has shown that embodiment in a virtual body of a different age alters participants' cognition and behavior in accordance with their virtual age (31,32). Building on these previous findings, Study 5 experimentally tested whether a virtual aging simulation can make young people more hopeful.…”
Section: Studymentioning
confidence: 89%
“…Virtual reality offers the unique possibility to temporarily substitute participants' physical body with a virtual body (30), which can have very different characteristics than their own, such as a different age. Previous research has shown that embodiment in a virtual body of a different age alters participants' cognition and behavior in accordance with their virtual age (31,32). Building on these previous findings, Study 5 experimentally tested whether a virtual aging simulation can make young people more hopeful.…”
Section: Studymentioning
confidence: 89%
“…Proteus effects were also observed in the context of pro-social and anti-social behaviors (Yoon & Vargas, 2014), product perception and purchasing behaviors (Yoo et al, 2015), and physical actions, like walking speed (Reinhard et al, 2020). Fox & Bailenson (2009) also demonstrated that the change in one's avatar's body affected their physical activities, although this study was based on social cognitive theory.…”
Section: Introductionmentioning
confidence: 86%
“…For instance, participants assigned to thin instead of obese avatars showed more physical activity while playing a motion-controlled tennis game (Peña et al, 2016). Relative to participants assigned to young avatar or a control group, participants who had earlier embodied older avatars took longer to walk a set distance (Reinhard et al, 2020).…”
Section: The Proteus Effectmentioning
confidence: 99%